Comparative analysis of President Susilo Bambang Yudhoyono and Joko Widodo’s food estate policies as a national food securitization attempts - Putri Audy Fahira; Jihan Amirotul Farikhah; Amouda Laula Nafila; Gita Adjipersadani; Philipus Mikhael Priyo Nugroho; A. Safril Mubah (Jurnal Sosiologi Dialektika, 2022)
Food-related issues affecting many people have long been a point of concern for nations, including Indonesia. President Susilo Bambang Yudhoyono (SBY) and Joko Widodo (Jokowi) had signed policies for food resilient policies that were riddled with problems such as land rights misallocation. Therefore, this research is conducted to answer research questions, including the comparison of food estate policies during the SBY and Jokowi, the act of securitization by both governments using food estate policies, and the inclusion of local farmers or people’s interest in the implementation of food estate policy strategies. The descriptive approach explains the impact and insufficiencies of policy implementation in their respective regimes. The comparison technique is called Qualitative Comparative Analysis (QCA), focusing on seeking the most similar out of the most different. The securitization concept is used to define a wide-ranging strategy utilized to reduce food vulnerabilities. This research showcased several differences between each regime’s national food securitization attempts, especially regarding the involvement of military mechanisms in Jokowi’s food estate. This research proved the existence of securitization attempts in each regime’s policy implementation, with problems relating to land access and lack of local farmers’ agencies. Researchers found that this is partially caused by limited government understanding surrounding food security, which only persisted on availability instead of sustainability.